BATIK ANOMART MEDIA ARTS EDUCATION CREATIVITY AND APPRECIATION: CASE STUDY UKM BATIK ANOMART IN KARTASURA - Moh. Yudik Al Faruq (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2020)
ABSTRACTBatik is a skill that has high artistic value and has become part of Indonesian culture. Pandono Batik Abstract has unique techniques, patterns and motifs, even more than others, so that it has one style and motif, only one in the world. Given that batik is written batik, the results of the patterns and motifs of Pandono Batik Abstract also have no limitations on certain standards, tend to be abstract and must always be different, this is the advantage of Batik Pandono Abstract Laweyan Surakarta. This research method is carried out by applying a qualitative approach. Qualitative research is a study conducted by conducting observations, observations and interviews. The strategy that will be used in this study is single-embedded. The purpose of this embedded research is that the research is directed at one goal (one location, or one subject) as its main focus. Nevertheless the parts studied are still related to the overall context to get full meaning.Keywords: Abstract batik, educational media, appreciation